Blue Economy Development and Income Inequality: a Dynamic Panel Analysis of Indonesian Provinces - Fradya Randa; Bunga Paramita; Sufnirayanti Sufnirayanti; Sri Ningsih; Lastri Anggi Fani (Poltanesa, 2026)
This study provides a dynamic panel analysis of the relationship between blue economy development and income inequality across 32 Indonesian provinces over the period 2019–2025. Focusing on the fisheries sector as a key and measurable component of blue economy activities in Indonesia, the analysis System GMM estimation to address endogeneity and Nickell bias, the analysis yields several key findings. Income inequality exhibits strong temporal persistence, with a lagged Gini coefficient of 0.8108, indicating that approximately 81% of inequality carries over from one year to the next. F isheries sector development , measured by the fisheries sector’s contribution to provincial GRDP, shows no statistically significant effect on income inequality at the aggregate level. Human capital development significantly reduces inequality. Heterogeneity analysis reveals that inequality persistence is higher in low blue economy provinces, than in high blue economy provinces. Human capital development remains a significant equalizing factor in both subsamples. These results show that the development of the fisheries sector in blue economies does not automatically translate into reduced inequality, The benefits of its distribution depend on the complement factors such as infrastructure, institutional capacity, and human capital investment. The findings offer important policy implications for designing more targeted and context sensitive blue economy strategies in Indonesia.